Biological control of Ralstonia solanacearum and its effect on the vegetative growth of organic banana - Ramos-Veintimilla, Mario; Zambrano-Gavilanes, Freddy; Solís-Hidalgo, Karina; Garcés-Fiallos, Felipe; Quimi Arce, Víctor; Sánchez-Urdaneta, Adriana (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The banana (Musa AAA) is one of the main economically important crops worldwide. Currently, it faces a serious problem of plant death caused by the bacterium Ralstonia solanacearum (Smith) variety 2. The objective of this research was to evaluate the effect of biological control of Moko disease and its relationship with the vegetative growth of banana seedlings under field conditions. Four treatments were employed: absolute control (T0), Trichoderma spp. (T2), Bacillus spp. (Bio-remedy) (T3), and ADMF® (T4) with three replications in a completely randomized block design. The incubation period, the incidence percentage, and the area under the disease progress curve (AUDPC) were evaluated, along with plant survival and height, pseudostem diameter, and leaf emission rate. At 113 days after transplanting (dat), treatments T1, T2, and T3 showed higher seedling survival. Plant height (111-145 cm), pseudostem diameter (7.43-11.28 cm), and leaf emission rate (11.74-13.15 leaves) exhibited significant differences among treatments. Treated plants showed the lowest AUDPC (between 576.1 and 1435.4 units) compared to untreated plants (3156.55 units). Trichoderma, Bacillus, and ADMF® were demonstrated to reduce disease incidence and promote banana vegetative growth, proving to be viable sustainable alternatives for this crop.